Pengembangan Profil Kepribadian Empati Konselor dalam Pemberian Layanan Bimbingan dan Konseling - Septiani, Dwi Intan; Hasanah, Rizkia Mufidatul; Baiti, Nur Fadila (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2020)
One of the characteristics of personal qualities that need to be possessed by a counselor is the skill of empathy. This empathy skill can be interpreted as a way for the counselor to place himself in the feelings of the response to the problems experienced by the counselee. Empathy skills are needed by counselors so that the counseling process can also run effectively and smoothly, in other words, counselors who have empathy and are accompanied by other characteristics can affect the effectiveness of their guidance and counseling services.